Tadeusz Joachimowski - the testimony of former prisoner from concentration camp Auschwitz II-Birkenau - Míšková, Anna (Romano džaniben, 2022)
The testimony of T. Joachimowski represents one of the fundamental sources for the history of the so-called family Gypsy camp in Auschwitz II-Birkenau. T. Joachimowski was imprisoned as a political prisoner in the Auschwitz concentration camp, and from March 1943, as a scribe, he became responsible for recording the prisoners in the section of the Auschwitz II-Birkenau extermination camp known as the family Gypsy camp. In July 1944, shortly before the destruction of the local Gypsy camp, he hid the two main record books, thus contributing to the preservation of a unique source on the fate of the Roma and Sinti families and individuals imprisoned there. The archives of the Auschwitz-Birkenau State Museum contain more documents related to Joachimowski. The testimony published here represents the most comprehensive account of his experiences. It was recorded in 1960 by Danuta Czech, who used it in her monumental publication The Auschwitz Chronicle. In it, T. Joachimowski touches on various aspects of the so-called Gypsy family camp at Auschwitz II - Birkenau. In addition to describing the camp itself and the living conditions in it, he also describes a fundamental act of resistance by the Roma and Sinti imprisoned there, which T. Joachimowski, in collaboration with Danuta Czech, dates to 16 May 1944. Thanks to the recent popularisation of this event, this date, commemorated annually as Romani Resistance Day, has become another important European/global commemorative day associated with the history of the Roma. The testimony of T. Joachimowski represents a key account of this event.